Respostas
respondido por:
3
11x-(-3x+10)=4x+2
11x+3x-10=4x+2
14x-4x=2+10
10x=12
x=12/10 (÷2)
x=6/ 5
11x+3x-10=4x+2
14x-4x=2+10
10x=12
x=12/10 (÷2)
x=6/ 5
AnaLarisse:
Obg❤
respondido por:
1
11x - (-3x + 10) = 4x + 2
11x + 3x - 10 = 4x + 2
14x - 10 = 4x + 2
14x - 4x = 2 + 10
10x = 12
x = 12/10
x = 6/5
11x + 3x - 10 = 4x + 2
14x - 10 = 4x + 2
14x - 4x = 2 + 10
10x = 12
x = 12/10
x = 6/5
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás